Respuesta :

Answer:

the answer is B

Step-by-step explanation:

since one equation is already simplified then you shall plug in the other  equation into the other to substitute and simplify

Answer:

3x+4(2x+4) = 17

Substitute (2x+4) for y in the second equation

Step-by-step explanation:

Given the simultaneous equation;

y = 2x+4...(1)

3x+4y = 17...(2)

The most efficient first step to take is substituting equation 1 which is y = 2x+4 into equation 2 as shown.

3x+4(2x+4) = 17

This will reduce the two unknown in an equation to just one making it easier to find the single variable.

It will reduce the equation to:

3x+8x+16 = 17

11x+16 = 17.

Hence, this option below is correct

3x+4(2x+4) = 17

Substitute (2x+4) for y in the second equation.